2008
DOI: 10.1254/jphs.fp0072365
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Coenzyme Q10 on Increased Oxidative and Nitrative Stress and Inflammation and Individual Metabolic Components Developing in a Rat Model of Metabolic Syndrome

Abstract: Abstract. Metabolic syndrome (MetS) is a group of cardiovascular risk factors, including visceral obesity, glucose intolerance, hypertension, and dyslipidemia. Increased oxidative and nitrative stress and inflammation and decreased endothelial function occur in an animal model of metabolic syndrome, SHR / NDmcr-cp (SHR / cp) rats. The present study investigated the effects of coenzyme Q10 (CoQ10), one of the important antioxidants, on the abnormal oxidative condition and characteristic components of metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 50 publications
3
44
0
1
Order By: Relevance
“…We have previously found similar results with aortas of SHR-cp and suggested that the protective effects of telmisartan are linked to decreased oxidative-nitrosative stress via reduction of a component of NADPH oxidase, independently of its antihypertensive effect (18). Furthermore, long-term administration of Coenzyme Q10, a strong antioxidant, to SHR-cp has been reported to prevent both increased oxidative-nitrative stress and vascular dysfunction in mesenteric arteries (34). Taken together, continuous production of peroxynitrite formed by the reaction of NO with superoxide via angiotension II in blood vessels may lead to gradual development of functional damage in SHR-cp.…”
Section: Discussionsupporting
confidence: 68%
“…We have previously found similar results with aortas of SHR-cp and suggested that the protective effects of telmisartan are linked to decreased oxidative-nitrosative stress via reduction of a component of NADPH oxidase, independently of its antihypertensive effect (18). Furthermore, long-term administration of Coenzyme Q10, a strong antioxidant, to SHR-cp has been reported to prevent both increased oxidative-nitrative stress and vascular dysfunction in mesenteric arteries (34). Taken together, continuous production of peroxynitrite formed by the reaction of NO with superoxide via angiotension II in blood vessels may lead to gradual development of functional damage in SHR-cp.…”
Section: Discussionsupporting
confidence: 68%
“…16) However, at present, many people take it as a nutritional supplement with the expectation that it will be effective in anti-aging or preventing metabolic syndrome. 17,18) There are a lot of reports stating that CoQ 10 has high anti-oxidant effects, which are useful in delaying aging of the body. 19,20) Awareness of health issues has been growing in Japan after the introduction of a system regulating "Food for Specified Health Use" (Tokuho), under which the use of "health claims" was allowed, in 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Doring et al [23] and Schmelzer et al [24] Page 19 of 42 [53]. In another study, anti-inflammatory properties of CoQ10 on serum CRP levels of baboons have also been observed, but only when combined with vitamin E. This modification of serum CRP level was associated with an increase blood total antioxidant status [54].…”
Section: Page 16 Of 42mentioning
confidence: 93%